Evaluation and effect of loss of constraint on master curve reference temperature of 20MnMoNi55 steel. (March 2015) - Bhowmik, Sumit; Sahoo, Prasanta; Acharyya, Sanjib Kumar; Dhar, Sankar; Chattopadhyay, Jayanta
Highlights: Master curve method is used in ductile to brittle transition regime. Fracture toughness of 20MnMoNi55 steel is estimated. Effect of loss of constraint on reference temperature is studied. Effect of temperature, thickness, crack length is determined. Triaxiality ratio is computed at failure loads using FE analysis. Abstract: The effect of test temperature, specimen thickness and crack to width ratio on master curve reference temperature in ductile to brittle transition range of 20MnMoNi55 steel is experimentally determined. To transfer the correlations from specimen to component level, the effect of loss of constraint on reference temperature is estimated through triaxiality ratio using finite element analysis. The experimental fracture toughness tests are simulated in ABAQUS and the value of triaxiality ratio is computed at failure loads and the same is used to characterize the effect of constraint on master curve reference temperature.